Optimalisasi Produksi dan Distribusi dengan Metode Simpleks dan Minimum Spanning Tree pada UMKM Tahun NR - Hutajulu, Stepani Pricilia; Sari, Rianita Puspa (Peneliti.net, 2024)
In the midst of increasingly fierce competition, companies need to develop and improve performance in order to achieve effectiveness and efficiency, and solve problems faster. Linear programming can be used in an effort to optimize the production activities of companies and MSMEs. Linear programming itself is a problem model using equations or inequalities in linear form. This research was conducted at UMKM Tahu NR which is located at Jl. Raden Kubaya, Karangpawitan, West Karawang, Kab. Karawang. This factory is one of the many MSMEs that produce tofu in Karawang and has 7 employees. MSME NR produces two types of tofu, namely white tofu and yellow tofu with a net profit of Rp. 8500 for white tofu and Rp. 8800 for yellow tofu. From the existing data processing it is known that the optimal production combination to obtain maximum profits is to produce 5250 packs of white tofu and 8750 packs of yellow tofu every week, with a profit of Rp. 121,625,000 every week. Determining distribution routes using the Minimum Spanning Tree method produces optimal route with a total distance of 21.2 km.